Evolving sediment dynamics due to anthropogenic processes in upper Chesapeake Bay. (5th April 2020) - Russ, Emily; Palinkas, Cindy
Abstract: Like many estuaries, the upper Chesapeake Bay effectively traps sediment from its tributaries and shorelines. However, evolving sediment dynamics from human influences such as increased soil conservation, dam construction (and subsequent infill), and increased shoreline stabilization have altered sediment loads to the Bay. Sediment budgets are important tools for evaluating sediment dynamics through identifying sources, sinks, and transport pathways. The most recent upper Bay sediment budget was developed >25 years ago and does not reflect the evolution of sediment delivery. The objective of this study is to develop an updated sediment budget through quantitative analysis of the upper Bay's major sediment sources (Susquehanna River and shoreline erosion) and sinks (deposition in the Susquehanna Flats region and mainstem Bay). Results indicate that Susquehanna River input to upper Bay has decreased during low flows, due to implementation of conservation-management strategies, but increased during high flows, from infilling of the Conowingo Reservoir. Inputs from shoreline erosion have decreased due to increased shoreline stabilization. Mass accumulation rates in the upper Bay generally decrease with distance downstream, but elevated sedimentation rates occur in deeper water, and possibly represent sediment focusing near channels. Insights gained from this study not only inform sediment management strategies in the Bay and similar systems, but also can help forecast potential future trajectories from environmental and anthropogenic drivers. For example, changing climate is projected to increase precipitation, storminess, and sea-level rise (SLR), which would increase both Susquehanna River and shoreline erosion sediment inputs. These changes could help the sedimentation rates keep pace with SLR but also may degrade downstream ecosystems due to increased fine-sediment input and turbidity. Shoreline stabilization will also likely increase, which would reduce shoreline erosion and thus sand inputs necessary for some nearshore benthic habitats to keep pace SLR. Highlights: Sediment-conservation practices have decreased watershed sediment loads. Sediment loads have increased with reservoir infilling under high-flow conditions. Increased shoreline protection has decreased shoreline erosion. Sedimentation rates are highest near the river mouth and decrease downstream.